THE EFFECT OF USING EDMODO APPLICATION ON THE STUDENTS’ WRITING SKILL OF ANALYTICAL EXPOSITION TEXT AT SMAN 4 PALANGKA RAYA - Enggal Pinanggih; Ristati Ristati; Wahyuningsih Usadiati (Intensive Journal, 2021)
This research was conducted to find out the effect using Edmodo application on the students’ writing skill of analytical exposition text at SMAN 4 Palangka Raya. Data of the students score of writing Analytical Exposition text was collected using writing test, and the hypothesis testing was examined based on t-test for normally because the data distribution was normal. A test in form of writing analytical exposition text was used the instrument to collect the data needed. Then, the data were analyzed by using parametric statistic dependent sample T – test because the data were normally distributed. The writer took conclusion based on statistical result. The result of this research shows that the critical value for students T distribution was 1.734 the critical value t0 was t05 {19} = 1.729. Because 1.734 is greater than 1.729, null hypothesis was rejected. Thus, it can be concluded that there was significant effect of using Edmodo Application in writing Analytical Exposition Text gained by eleventh grade of SMAN 4 Palangka Raya. Thus, Edmodo Application had been successful in improving students’ writing ability of Analytical Exposition text. The researcher suggest that the teacher should provide an appropriate media in teaching English, especially for Analytical Exposition Text and made Edmodo Application as reference to him/her to use it for making students’ attracted to the material.